2022
DOI: 10.3390/antibiotics11050553
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antifungal Activity of Synthetic Peptides and Antifungal Drugs against Candida albicans and C. parapsilosis Biofilms

Abstract: C. albicans and C. parapsilosis are biofilm-forming yeasts responsible for bloodstream infections that can cause death. Synthetic antimicrobial peptides (SAMPs) are considered to be new weapons to combat these infections, alone or combined with drugs. Here, two SAMPs, called Mo-CBP3-PepI and Mo-CBP3-PepIII, were tested alone or combined with nystatin (NYS) and itraconazole (ITR) against C. albicans and C. parapsilosis biofilms. Furthermore, the mechanism of antibiofilm activity was evaluated by fluorescence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 34 publications
4
20
0
Order By: Relevance
“…On the contrary, the synthetic peptide #14d did not cause ROS overproduction in C. albicans ATCC 10231 biofilm, which are involved in the disruption of essential molecules such as proteins, lipids, and DNA. This result corroborates those reported by Bezerra and collaborators [ 43 ], who showed the absence of ROS overproduction by C. albicans biofilm after treatments with the conventional antifungal agents nystatin and itraconazole. MD simulations performed on this peptide further suggested that the displayed antifungal activity could be partially related to the overall wide distribution of the positive electrostatic charge in its three-dimensional structure.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…On the contrary, the synthetic peptide #14d did not cause ROS overproduction in C. albicans ATCC 10231 biofilm, which are involved in the disruption of essential molecules such as proteins, lipids, and DNA. This result corroborates those reported by Bezerra and collaborators [ 43 ], who showed the absence of ROS overproduction by C. albicans biofilm after treatments with the conventional antifungal agents nystatin and itraconazole. MD simulations performed on this peptide further suggested that the displayed antifungal activity could be partially related to the overall wide distribution of the positive electrostatic charge in its three-dimensional structure.…”
Section: Discussionsupporting
confidence: 93%
“…Of particular importance, the synthetic derivative peptide #14d (FHLVWRAGGTF), selected on the basis of three advantageous chemical-physical parameters (percentage of hydrophobic ratio, charge, Boman index), due to its interesting antifungal activity and low toxicity toward human cells in vitro, may represent a good therapeutic candidate worthy to be developed against the pathogen C. albicans . Peptide #14d inhibited the growth of C. albicans ATCC 10231 through cell membrane damage causing death [ 41 , 42 , 43 ]. The peptide showed indicative anticandidal activity, revealing a MIC value equal to 31.2 μg/mL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, synthetic antimicrobial peptides have emerged as potential candidates because they are based on natural antimicrobial peptides but have high activity and low toxicity levels [5][6][7]. In addition to being employed alone, synthetic peptides could be applied synergistically with commercial drugs to improve their action [8][9][10][11]. For Disclaimer/Publisher's Note: The statements, opinions, and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s).…”
Section: Introductionmentioning
confidence: 99%